SO 2009 - ord - Språkbanken Text (University of Gothenburg, 2025)
Words in Svensk ordbok.

Ord i Svensk ordbok.
SO 2009 - ord
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik